Simultaneous electrochemical detection of dopamine and ascorbic acid using iron oxide/reduced graphene oxide modified glassy carbon electrode - Teo, Peik See; Pandikumar, Alagarsamy; Huang, Nay Ming; Lim, Hong Ngee; Sulaiman, Yusran (MDPI, 2014)
The fabrication of an electrochemical sensor based on an iron oxide/graphene modified glassy carbon electrode (Fe3O4/rGO/GCE) and its simultaneous detection of dopamine (DA) and ascorbic acid (AA) is described here. The Fe3O4/rGO nanocomposite was synthesized via a simple, one step in-situ wet chemical method and characterized by different techniques. The presence of Fe3O4 nanoparticles on the surface of rGO sheets was confirmed by FESEM and TEM images. The electrochemical behavior of Fe3O4/rGO/GCE towards electrocatalytic oxidation of DA was investigated by cyclic voltammetry (CV) and differential pulse voltammetry (DPV) analysis. The electrochemical studies revealed that the Fe3O4/rGO/GCE dramatically increased the current response against the DA, due to the synergistic effect emerged between Fe3O4 and rGO. This implies that Fe3O4/rGO/GCE could exhibit excellent electrocatalytic activity and remarkable electron transfer kinetics towards the oxidation of DA. Moreover, the modified sensor electrode portrayed sensitivity and selectivity for simultaneous determination of AA and DA. The observed DPVs response linearly depends on AA and DA concentration in the range of 1–9 mM and 0.5–100 µM, with correlation coefficients of 0.995 and 0.996, respectively. The detection limit of (S/N = 3) was found to be 0.42 and 0.12 µM for AA and DA, respectively.